Oil Exports and Economic Growth: An Empirical Evidence from Saudi Arabia - Sultan, Zafar Ahmad; Haque, Mohammad Imdadul (International Journal of Energy Economics and Policy, 2018)
Being oil-based economy, the economic prosperity of Saudi Arabia to a large extent depends upon international price of crude oil. Since substantial portion of government revenue and foreign exchange which determine the economic activities of the government and fulfill the import requirements of the country comes from oil exports, any disturbance in this sector is likely to affect entire economy of Saudi Arabia. The paper applied Johansen cointegration method and vector error correction model (VECM) to estimate long run relationship of economic growth with oil exports, imports and government consumption expenditure. The study has found that economic growth has long run relationship with oil exports, imports and consumption expenditure of the government. The study recommends monitoring and regulating imports and intensive efforts to diversify economic base in exports as well as import substituting industries of the country. Keywords: Oil Export, Economic Growth, Causality, Saudi Arabia JEL Classifications: C22, F14, H50, N15